The Influence of Social Dimension, Financial Flexibility Dimension and Environmental Dimension (Triple Bottom Line) on The Management Accounting Information System in Regional General Hospitals in East Java Province - suwondo, ontot murwato (Archives of Business Research, 2018)
The core of Management Accounting Information System (MAIS) is a process; determined by activities such as collecting, measuring, storing, analyzing, reporting, and managing information. MAIS is useful for decision making and performance evaluation in manufacturing companies, trading and service. Today, wise business is the one that balances the financial, social and environmental aspects (Triple Bottom Line/TBL). Based on this phenomenon, the study entitled The Influence of Social Dimension, Financial Flexibility Dimension and Environmental Dimension (Triple Bottom Line) on the Management Accounting Information System in Regional General Hospitals in East Java Province was conducted. The population in this study was 183 work units in 4 (four) Regional General Hospitals (RSUD) of East Java Provincial Government. This research belongs to the positivism paradigm, thus hypothesis testing is an important stage. SPSS was employed to test the validity and reliability of the questionnaire. For the model (outer and inner model) testing and hypothesis testing, Variance-Based SEM, PLS (smart PLS 3.0) was used. Hypothesis test results showed that: 1) The financial dimension had a significant effect on MAIS; 2) The financial flexibility dimension had a significant effect on MAIS; 3) The environmental dimension had a significant effect on MAIS.